Students’ Perception on Digital Storytelling in Speaking Class of English Department - Firda Amelia; Bibit Suhatmady; Noor Rachmawaty (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2023)
Digital storytelling has been utilized as a method to help students improve their speaking abilities. This research is conducted to explore the use of Digital Story Telling method to help teaching and learning process in English department students of Mulawarman University to develop their ability to speak English. This study used a descriptive qualitative design to analyze the data. The subjects of the study were three students of English Teaching and Learning faculty Academic year 2019. The instrument used in this study were their English speaking score as documents and interview questions. The result showed that using digital story telling made students learn through various ways of learning by using all creative skills they have which was interesting and useful. Digital storytelling affecting both of the students’ hard skill and soft skill. Students were also motivated to improve the vocabularies and pronunciation of English speaking skill they have already possessed.